2012
DOI: 10.1016/j.chom.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

The UPEC Pore-Forming Toxin α-Hemolysin Triggers Proteolysis of Host Proteins to Disrupt Cell Adhesion, Inflammatory, and Survival Pathways

Abstract: SUMMARY Uropathogenic Escherichia coli (UPEC), which are the leading cause of both acute and chronic urinary tract infections, often secrete a labile pore-forming toxin known as α-hemolysin (HlyA). We show that stable insertion of HlyA into epithelial cell and macrophage membranes triggers degradation of the cytoskeletal scaffolding protein paxillin and other host regulatory proteins, as well as components of the proinflammatory NFκB signaling cascade. Proteolysis of these factors requires host serine protease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
146
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(155 citation statements)
references
References 70 publications
7
146
0
2
Order By: Relevance
“…One possible explanation is that HlyA disrupts NF-kB signaling via activation of host serine proteases as described during UTI. 30 Such a hypothesis is consistent with our findings that HlyA acts downstream from the activation of Rac and upstream from the secretion of IL-1beta. This provides further evidence of the importance of pathogens to target the caspase-1/IL-1beta signaling axis.…”
Section: Neutralizing Rho Gtpases Downstream Effects To Block Avi Andsupporting
confidence: 90%
“…One possible explanation is that HlyA disrupts NF-kB signaling via activation of host serine proteases as described during UTI. 30 Such a hypothesis is consistent with our findings that HlyA acts downstream from the activation of Rac and upstream from the secretion of IL-1beta. This provides further evidence of the importance of pathogens to target the caspase-1/IL-1beta signaling axis.…”
Section: Neutralizing Rho Gtpases Downstream Effects To Block Avi Andsupporting
confidence: 90%
“…HlyA-positive isolates have been shown to stimulate more rapid and extensive shedding of human BECs than isogenic hlyA-negative mutant strains (11,12). HlyA-mediated exfoliation is, in part, due to its ability to trigger degradation of paxillin, a scaffold protein that can modulate the dynamics of cytoskeletal rearrangements (14). Here, we discovered that overexpression of the hlyA gene in UPEC triggers urothelial cell death and release of IL-1α via hCaspase-4 activation and Caspase-1-dependent IL-1β secretion via activation of the NLRP3 inflammasome pathway to orchestrate additional cell death.…”
Section: Overproduction Of Hlya Increases Bladder Inflammasome Activamentioning
confidence: 99%
“…HlyA can form pores in the membranes and lyse a number of mammalian cell types, including RBCs (13). Recent studies have shown that HlyA can trigger rapid degradation of paxillin and other host proteins involved in cell-cell and cell-matrix interactions, a mechanism thought to promote exfoliation (14). In Staphylococcus aureus, hemolysins in the presence of lipoproteins promote the activation of Caspase-1 via the inflammasome in monocytic cells (15).…”
mentioning
confidence: 99%
“…28, 2018; (which was not peer-reviewed) is the author/funder, who has granted bioRxiv a license to display the preprint in perpetuity. constructed by introducing into the wild-type strain (EIB202, CCTCC M208068) the plasmid 632 of pSF4000-hlyBACD (Dhakal & Mulvey, 2012) into UPEC UT189, EHEC EDL933 (Burgos et 633 al, 2009), EPEC (E. coli O26) (Schmidt et al, 1995) and K12, respectively. 634 .…”
Section: Conflict Of Interest 389mentioning
confidence: 99%